Remission and low disease activity (LDA) prevent damage accrual in patients with systemic lupus erythematosus: results from the Systemic Lupus International Collaborating Clinics (SLICC) inception cohort. Issue 11 (9th August 2022) - Ugarte-Gil, Manuel Francisco; Hanly, John; Urowitz, Murray; Gordon, Caroline; Bae, Sang-Cheol; Romero-Diaz, Juanita; Sanchez-Guerrero, Jorge; Bernatsky, Sasha; Clarke, Ann Elaine; Wallace, Daniel J; Isenberg, David Alan; Rahman, Anisur; et al.
Abstract : Objective: To determine the independent impact of different definitions of remission and low disease activity (LDA) on damage accrual. Methods: Patients with ≥2 annual assessments from a longitudinal multinational inception lupus cohort were studied. Five mutually exclusive disease activity states were defined: remission off-treatment: clinical Systemic Lupus Erythematosus Disease Activity Index (cSLEDAI)-2K=0, without prednisone or immunosuppressants; remission on-treatment: cSLEDAI-2K score=0, prednisone ≤5 mg/day and/or maintenance immunosuppressants; low disease activity Toronto cohort (LDA-TC): cSLEDAI-2K score of ≤2, without prednisone or immunosuppressants; modified lupus low disease activity (mLLDAS): Systemic Lupus Erythematosus Disease Activity Index-2K score of 4 with no activity in major organ/systems, no new disease activity, prednisone ≤7.5 mg/day and/or maintenance immunosuppressants; active: all remaining visits. Only the most stringent definition was used per visit. Antimalarials were allowed in all. The proportion of time that patients were in a specific state at each visit since cohort entry was determined. Damage accrual was ascertained with the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI). Univariable and multivariable generalised estimated equation negative binomial regression models were used. Time-dependent covariates were determined at the same annual visit as the disease activity state but the SDI at the subsequent visit. Results: There were 1652 patients, 1464 (88.6%) female, mean age at diagnosis 34.2 (SD 13.4) years and mean follow-up time of 7.7 (SD 4.8) years. Being in remission off-treatment, remission on-treatment, LDA-TC and mLLDAS (per 25% increase) were each associated with a lower probability of damage accrual (remission off-treatment: incidence rate ratio (IRR)=0.75, 95% CI 0.70 to 0.81; remission on-treatment: IRR=0.68, 95% CI 0.62 to 0.75; LDA: IRR=0.79, 95% CI 0.68 to 0.92; and mLLDAS: IRR=0.76, 95% CI 0.65 to 0.89)). Conclusions: Remission on-treatment and off-treatment, LDA-TC and mLLDAS were associated with less damage accrual, even adjusting for possible confounders and effect modifiers.